Experimental investigation on the water entry of a bulbous bow based on TR-PIV. (1st June 2021) - She, Wenxuan; Zhou, Guangli; Guo, Chunyu; Wu, Tiecheng; Song, Kewei
Abstract: The objective of this work is to experimentally investigate the dynamic evolution of flow structure and pressure distribution on the water entry of a bulbous bow. We focus on the water entry of an arbitrary bow based on the 18.5 station line of the KRISO container ship with a typical bulbous bow. Time-resolved particle image velocimetry (TR-PIV) is utilized to capture the transient flow information during the bow slamming. The instantaneous pressure is estimated by solving the incompressible Navier–Stokes equation using the Lagrangian approach. Our findings demonstrate the formation and migration of a saddle point, the generation of a strong shear layer near the concave zone at a low initial velocity, and the deformation of an air pocket at a high initial velocity. Furthermore, we offer insight into the reconstructed pressure field over the entire duration of the slamming, especially the dramatic slamming pressure during the secondary impact. It is interesting that the peak value locates on the critical point of the upward and downward flow caused by the pressing of the bow flare. In addition, the pressure close to the flare continuously keeps the global maximum. Highlights: Water entry experiments of a bulbous bow were performed during the slamming. Various flow scenarios with or without separation were captured using TR-PIV. The slamming pressure was reconstructed to offer insight into the secondary impact.